2019
DOI: 10.4172/2155-9864.1000413
|View full text |Cite
|
Sign up to set email alerts
|

CALR and CD47: An Insight into Their Roles in the Disease Progression of MDS and MPN

Abstract: Myelodysplastic syndrome and myeloproliferative neoplasms are clonal myeloid disorders arising from haematopoietic stem cells that have the tendency to progress into acute myeloid leukaemia. Multiple prognostic scoring systems have been proposed and utilised in clinical practice to predict disease evolution, however none of them can predict treatment response. In solid tumours, the relationship between the pro-phagocytic calreticulin and the anti-phagocytic CD47 is repeatedly investigated. Overexpression of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In preclinical studies, azacitidine was found to simultaneously upregulate cell surface expression of both CD47 and calreticulin in AML and MDS cell lines [ 72 , 73 ]. In vitro, azacitidine plus magrolimab synergistically increased macrophage-mediated phagocytosis of AML cells which translated into a significant improvement in the long-term survival of AML xenograft mouse models [ 71 ].…”
Section: Cd47-sirpα Blockadementioning
confidence: 99%
“…In preclinical studies, azacitidine was found to simultaneously upregulate cell surface expression of both CD47 and calreticulin in AML and MDS cell lines [ 72 , 73 ]. In vitro, azacitidine plus magrolimab synergistically increased macrophage-mediated phagocytosis of AML cells which translated into a significant improvement in the long-term survival of AML xenograft mouse models [ 71 ].…”
Section: Cd47-sirpα Blockadementioning
confidence: 99%
“…AZA has been shown to both increase expression of CD47 and the pro-phagocytic signal calreticulin in myeloid malignancies. AZA synergizes with MAGRO by inducing “eat me” signals on AML, to enhance phagocytosis [ 58 ].…”
Section: Hma In Combination With Other Drugs In Aml and Mds With ...mentioning
confidence: 99%
“…For anti-tumor activity, another co-stimulatory signal is needed. Tumor cells may need to express additional pro-phagocytic signals such as SLAMF7 with Mac-1 [ 92 ] and calreticulin induced by azacitidine, [ 93 ] or additional activation of macrophages via Fcγ receptor activation by the Fc region of a monoclonal antibody targeting CD47 or by a second agent targeting leukemia cells (e.g., CD33). Preclinical findings have also shown that F(ab’)2 fragments of a monoclonal antibody against CD47 showed no apoptotic effect on CD34+ hematopoietic progenitor/stem or human endothelial cells in leukemia xenograft mouse models [ 94 ].…”
Section: Anti-cd47 Antibodiesmentioning
confidence: 99%